(untitled) (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Expert System is one of artificial Intelligence which uses the knowledge of an expert as its knowledge base. In this research, expert system designed to diagnosing bipolar disorder using the method of bayesian network. The result of this application is the type of psychiatric diseases bipolar and the value of the probability of each disease. In this research, the probability of bipolar disorder test data according to medical records obtained yield was 39.39% and the results of testing using test data with new symptoms obtained yield was 55.55%. Key words Bayesian network, bipolar disorder,expert system